Somatotype, role and performance in elite volleyball players - Gualdi-Russo, E.; Zaccagni, L. (The Journal of Sports Medicine and Physical Fitness, 2001)
The purpose of the present study was to examine the importance of the somatometric components of elite male and female volleyball players in relation to their different game roles and levels of performance. METHODS: Two hundred and thirty-four male athletes (aged 24.7+/-4.4 years) and 244 female athletes (aged 23.1+/-4.4 years) from the Italian A1 and A2 volleyball leagues underwent anthropometric measurements during the 1992-1993 and 1993-1994 seasons. Somatotypes were estimated with the Heath-Carter method. RESULTS: Marked sexual dimorphism in somatotype was observed in the total sample. The average somatotype for men was 2.2-4.2-3.2 (SD 0.7-0.9-0.9), and for women it was 3.0-3.3-2.9 (SD 0.8-1.0-0.9). The somatotype was significantly different in players at different levels of performance (A1 vs A2 leagues), as it follows: 2.1-4.1-3.3 (SD 0.6-0.8-0.7) vs 2.3-4.3-3.0 (SD 0.7-1.0-0.8) in males; 2.9-3.1-3.0 (SD 0.8-1.0-0.9) vs 3.1-3.5-2.7 (SD 0.8-0.9-0.8) in females. The somatotype was also significantly different in players in different roles. In male sex the mean somatotypes for setters were 2.4-4.5-2.8 (SD 0.7-0.9-0.8), for centres they were 2.0-4.0-3.5 (SD 0.6-1.0-0.8), for spikers they were 2.2-4.3-3.0 (SD 0.6-0.9-0.7), for opposites they were 2.2-4.3-3.1 (SD 0.6-0.9-0.8). In female sex the mean somatotypes for setters were 3.1-3.6-2.5 (SD 0.8-1.0-1.0), for centres they were 2.8-3.1-3.1 (SD 0.8-0.9-0.7), for spikers they were 3.0-3.5-2.8 (SD 0.9-1.0-0.9) and for opposites they were 3.0-3.2-3.0 (SD 0.7-0.9-0.8). CONCLUSIONS: The physique of athletes in the A1 league is characterized by higher ectomorphy and lower endomorphy and mesomorphy. There is also a slight tendency of male players to a greater homogeneity in somatotype within the group at the maximum level of performance. Moreover somatotype differs in relation to game role in volleyball players of both sexes: the mesomorphic component is maximal in setters, while the ectomorphic component is maximal in centres.